Zirconium phosphate nano-platelets: a novel platform for drug delivery in cancer therapy - Díaz, Agustín; Saxena, Vipin; González, Julissa; David, Amanda; Casañas, Barbara; Carpenter, Carrie; Batteas, James D.; Colón, Jorge L.; Clearfield, Abraham; Delwar Hussain, M. (Chemical communications (Cambridge, England), 2012)
Doxorubicin was intercalated into novel zirconium phosphate nano-platelets (ZrP). The obtained doxorubicin intercalated ZrP nano-platelets had an impressive 34.9% (w/w) drug loading. We used this material to deliver doxorubicin to breast cancer cells (MCF-7). Cellular studies with MCF-7 cells showed higher uptake and cytotoxicity of doxorubicin loaded ZrP compared to free doxorubicin.